Studi Komunikasi: Aplikasi Qaulan Syakila dalam Membangun Masyarakat Islami - Achmad Fadly; Azhar (Jurnal Indonesia : Manajemen Informatika dan Komunikasi, 2024)
This research aims to determine the application of qaulan syakila in building an Islamic society. This research uses a qualitative descriptive method as an effort to identify natural problems within the scope of Islamic society related to communication. This research is an analytical study which uses the literature review as a data source and as a review unit for studying Islamic society as an object. The findings of this research were analyzed through data reduction, data presentation, and data verification. In creating valid data, researchers used triangulation. The results of this research show that, the application of qaulan syakila as a communication concept in Islamic society is a strong means for building deep understanding and strengthening religious values. Messages delivered in heavy, thoughtful words have the potential to stimulate thought, inspire action, and create long-lasting impact. Apart from that, Qaulan syakila also plays a role in forming religious identity, spreading Islamic teachings wisely, and building social solidarity. By speaking with wisdom and truth, Islamic communities can prove that religious values can be realized in every aspect of life, creating a society that is just, developed, and loyal to the roots of their traditions and culture.